Ventilatory Support, Extubation, and Cerebral Perfusion Changes in Pre-Term Neonates: A Near Infrared Spectroscopy Study - Paolo Massirio; Valentina Cardiello; Chiara Andreato; Samuele Caruggi; Marcella Battaglini; Andrea Calandrino; Giulia Polleri; Federica Mongelli; Mariya Malova; Diego Minghetti; Alessandro Parodi; Maria Grazia Calevo; et al. (Neurotrauma Reports)
Early extubation is considered to be beneficial for pre-term neonates. On the other hand, premature extubation can cause lung derecruitment, compromised gas exchange, and need for reintubation, which may be associated with severe brain injury caused by sudden cerebral blood flow changes. We used near infrared spectroscopy (NIRS) to investigate changes in cerebral oxygenation (rScO2) and fractional tissue oxygen extraction (+) after extubation in pre-term infants. This is a single-center retrospective study of NIRS data at extubation time of all consecutive pre-term neonates born at our institution over a 1-year period. Comparison between subgroups was performed. Nineteen patients were included; average gestational age (GA) was 29.4 weeks. No significant change was noted in rScO2 and cFTOE after extubation in the whole population. GA and germinal matrix hemorrhage (GMH)-intraventricular hemorrhage (IVH) showed a significant change in rScO2 and cFTOE after extubation. A significant increase in cFTOE was noted in patients with previous GMH-IVH (+0.040; p = 0.05). To conclude, extubation per se was not associated with significant change in cerebral oxygenation and perfusion. Patients with a diagnosed GMH-IVH showed an increase in cFTOE, suggesting perturbation in cerebral perfusion suggesting further understanding during this challenging phenomenon. Larger studies are required to corroborate our findings.